Effect of Implementing Bureaucracy Reform, Apparatus Competence, and Organizational Commitment to The Quality of Public Service in North Gorontalo District - et. al., Ridwan Yasin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bureaucratic reform is intended as an effort to increase the leadership capacity, knowledge, skills and attitudes of the apparatus as a public servant apparatus, all of which lead to concrete efforts from the role of government institutions in improving the quality of public services. This study uses a quantitative approach with ex post facto methods, primary and secondary data collection techniques. Processing the respondent's data using the Ms Exel program and the SPSS version 21 data processor Softwer, in order to analyze the respondent's profile including, Gender, Education level, Characteristics of respondents based on position group, and Characteristics of Respondents based on tenure The process of data analysis stages using the PLS-SEM method. The results showed that bureaucratic reform had a positive and significant effect on Organizational Commitment, where the resulting t-statistic value was 5,197 greater (> 1.96) than the t-table value, and alpha was significant at 5%. Apparatus competence has a significant effect on the quality of public services, where the resulting t-statistical path coefficient is greater than the t-table value of 2.974> 1.96. with an alpha significant level of 5%. Organizational Commitment has a positive and significant effect on the Quality of Public Services, where the resulting t-statistical path coefficient is greater than the t-table value of 4.554> 1.96 with a significant alpha level of 5%.